Personality differences in two minnow populations that differ in their parasitism and predation risk - Kortet, Raine; Sirkka, Ilkka; Lai, Yi-Te; Vainikka, Anssi; Kekäläinen, Jukka (Frontiers in Ecology and Evolution, 2015)
Animals are often individually consistent in their behavior, not only over time, but also across different functional contexts. Recent research has focused on phenotypic and evolutionary mechanisms explaining such personality differences through selection. Parasitism and predation induce important mortality and fitness costs, and are thus the main candidates to create and maintain personality differences in the wild. Here, we present data on the behavioral consistency of the Eurasian minnow (Phoxinus phoxinus) from two populations that live in different tributaries of the same river, but whose ecological environment differs fundamentally with regard to predation and parasitism. We experimentally demonstrate that minnow in both study populations are consistent in their boldness and activity. However, the two study populations differ notably: in the high predation and parasitism risk population fish show higher mean boldness, but tend to be less active than fish in low predation and parasitism risk population. Parasite (Diplostomum phoxini) load was negatively, but not statistically significantly, associated with fish activity level. Our study suggests that parasitism and predation are likely important agents in the ecology and evolution of animal personalities.